Prevalência de variantes associadas à resistência aos inibidores de protease em hemodialisados e transplantados renais com infecção pelo virus da hepatite C - Tavares, Rita Chelly Felix [UNIFESP] (2016)
NS3 protease inhibitors (PIs) were the first direct antiviral agents (DAAs) for the treatment of hepatitis C virus. The combination of second-wave PIs with other DAAs permitted the use of interferon-free regimens for chronic kidney disease (CKD) patients on dialysis and renal transplant (RTx) recipients, populations in which the use of interferon and ribavirin is limited. However, the occurrence of PI resistance-associated variants (RAVs), both baseline and induced by therapy, has resulted in the failure of many treatment strategies. The aim of this study was to estimate the prevalence of PI RAVs and of the Q80K polymorphism in CKD patients on hemodialysis (HD) and RTx recipients. Direct sequencing of the NS3 protease was performed in 67 patients (32 HD and 35 RTx). RAVs to PIs were detected in 18% of the patients: V55A (9%), V36L (1.5%), T54S (1.5%), S122N (1.5%), I170L (1.5%), and M175L (1.5%). Only 1.5% of the patients carried the Q80K polymorphism. The frequency of these mutations was more than two times higher in patients infected with GT1a (25%) than GT1b (9.7%) (p=0.1). The mutations were detected in 20% of treatment-naïve patients and in 15.6% of peginterferon/ribavirin-experienced patients (p=0.64). Furthermore, no mutation that would confer high resistance to PIs was detected. We conclude that the Q80K polymorphism was rare in the population studied. The occurrence of RAVs was common, with predominance in GT1a. However, the variants observed were those associated with low-level of resistance to PIs, facilitating the use of these drugs in this special group of patients.